Life in the Hitler Youth - Keeley, Jennifer, 1974- (San Diego, CA : Lucent Books, 2000)
Discusses life among the Hitler Youth, including their ideology and activities, school and home life, and involvement in World War II.
Includes bibliographical references (p. 101-106) and index.
Wilson's Senior High School, November 2002
School Library Journal, March 2000
Book Links (A.L.A.), January 2000
7.3
5-8
Keywords: Hitler Youth; National socialism; Germany -- Politics and government